Effects of Ultramicronized N-Palmitoylethanolamine Supplementation on Tramadol and Oxycodone Analgesia and Tolerance Prevention - Laura Micheli; Elena Lucarini; Alessandra Toti; Valentina Ferrara; Clara Ciampi; Carmen Parisio; Gianluca Bartolucci; Lorenzo Di Cesare Mannelli; Carla Ghelardini (Pharmaceutics, 2022)
Chronic pain management requires increasing doses of opioids, the milestone of painkillers, which may result in the onset of tolerance with exacerbated side effects. Maintaining stable analgesia with low doses of opioids is thus imperative. N-palmitoylethanolamine (PEA) is an endogenous lipid compound endowed with pain-relieving as well as anti-inflammatory properties. The ultramicronized formulation of PEA was recently demonstrated to be able to modulate morphine’s effects, delaying tolerance and improving efficacy. To evaluate the possible application to other opioids, in this study, we analysed the capacity of ultramicronized PEA to regulate analgesia and tolerance induced by oxycodone and tramadol. Pre-emptive and continuative treatment with ultramicronized PEA (30 mg kg−1, daily, per os) delayed the onset of opioid tolerance and enhanced opioid analgesia when it was acutely administered in association with tramadol (20 mg kg−1, daily, subcutaneously) or oxycodone (0.5 mg kg−1, daily, subcutaneously). Moreover, PEA exerted antinociceptive effects on tolerant rats, suggesting the use of PEA together with opioids for stable, long-lasting analgesia. To that purpose, the oxycodone dose needed to be increased from 0.3 mg kg−1 (day 1) up to 1 mg kg−1 (day 31) in the oxycodone + vehicle group; the tramadol dose was progressively enhanced from 15 mg kg−1 to 50 mg kg−1 in 31 days in the tramadol + vehicle group. Acute oral co-treatment with PEA (120 mg kg−1) achieved the same analgesia without increasing the dose of both opioids. The behavioural effects of PEA on opioid chronic treatment paralleled a decrease in astrocyte activation in the dorsal horn of the spinal cord (a marker of the development of opioid tolerance) and with a modulation of mRNA expression of IL-6 and serpin-A3. In conclusion, pre- and co-administration of ultramicronized PEA delayed the development of tramadol tolerance, potentiating either oxycodone or tramadol analgesia and allowing a long-lasting analgesic effect with a low opioid dose regimen. The use of PEA is suggested for clinical purposes to support the opioid-based management of persistent pain.